Reimagining Music Education: School–Community Partnerships for Cultural Sustainability in Indonesia - Nuristama , Ramadhina Ulfa (Harmonia : Journal of Music and Arts, 2024)
This study investigates how school–community partnerships can serve as effective models for integrating traditional music into formal education in Indonesia. With the rise of culturally responsive frameworks such as Kurikulum Merdeka and global attention on intangible cultural heritage, there is an increasing need to explore how education systems can preserve and promote cultural identity through collaborative initiatives. The objective is to examine the structures, impacts, and challenges of such partnerships across different educational contexts. Employing a qualitative multi site case study design, the research focuses on three schools engaged in different types of collaboration with local cultural institutions, including co teaching, guest artist residencies, and service learning. Data were collected through semi structured interviews, participant observation, and document analysis. Thematic analysis was conducted using NVivo software to identify key patterns and stakeholder perspectives. Findings reveal that school–community partnerships significantly enhance students’ cultural literacy, self expression, collaboration skills, and performance confidence. Traditional music education was found to be most effective when delivered through experiential and reflective approaches, supported by mutual planning between educators and cultural practitioners. Community involvement provided authenticity and fostered stronger student engagement. Moreover, the study confirms the applicability of frameworks such as UNESCO’s “Teaching with Living Heritage” and Culturally Sustaining Pedagogy, both of which emphasize cultural continuity and identity development. Key challenges included scheduling conflicts, limited resources, and unclear role definitions all of which were mitigated through flexible planning, digital tools, and written agreements. In conclusion, this research contributes a scalable and context sensitive model for integrating traditional music into national education. It underscores the value of schools acting as cultural agents and highlights the importance of policy support for inclusive, culturally embedded education.